Racism and "Place" in American Catholic Experience. Issue 1 (5th April 2019) - Hoang, Linh
Abstract : Racism occurs in place. It is any place where human beings dwell such as a certain location, a house, or even a church. Racism is a lived experience that exposes the tragedy of hate and fear of the other. It pushes people into uncomfortable places. Asian Americans have built enclaves across the United States in order to maintain their cultural identity and help in resettlement. These ethnic enclaves have become, however, a way to silence and sideline Asians from the racial debates that has traditionally pitted blacks and whites for centuries. Asians have "assimilated" well into the dominant white culture but have not been completely accepted instead they continue to experience discrimination and prejudices. Even in the Church, Asian American Catholics struggle for recognition of their contribution and participation. The process of reconciliation that Robert J. Schreiter has elaborated provides an opportunity for Asian American Catholics to engage in the racial conversation while improving the Church's place in healing racism.